Sonata para violoncelo e piano de José Vieira Brandão: um estudo analítico-musicológico voltado para a performance - Azevedo, Isabelle Sousa (2021)
This research approaches aspects of José Vieira Brandão's Sonata for cello and piano, from an analytical-interpretative approach, intended to support interpreters in theirs performance decisions. The study demonstrates how Vieira Brandão, an exceptional pianist, from his experience with Villa-Lobos, became the main interpreter of his work and, through this proximity, he discovered himself a remarkable composer. Therefore, the research seeks to elucidate the influence of Villa-Lobos in the elaboration of a Sonata for cello and piano based on clearly Brazilian elements. In the case of Vieira Brandão's music, we can verify that the composer adopts paths already trodden by Villa-Lobos, without losing his own compositional identity. In the study of the work, it is possible to observe technical and compositional aspects relevant to the cello, such as the use of idiomatic language as well as the exploration of new timbers for that instrument, combined with the element of Brazilianism. The research has as theoretical reference based on authors such as Rodrigues (2017), Borges (2004) and Fischer (2001). Furthermore, as an analytical-theoretical framework, authors such as Cone (1968), Réti (1978), Green (1979), Cook (1987) and Aquino; Aquino (2021) are being used. From the contextualization of the composer in the Brazilian music scene of the 20th century, it is intended to establish his stylistic characteristics, through an analytical and bibliographic survey about the composer, music educator, and interpreter. Furthermore, they were chosen with researchers and interpreters of Brazilian music relevant to research, such as Hugo Pilger and Lucia Barrenechea, who recorded the work in question. A critical edition of the work was also produced based on a fair copy made by copyist Carlos Gaspar. Thus, we imagine that this research might leave a significant contribution to the expansion of the Brazilian musical repertoire for the cello.